The Process of Self-Management: A Qualitative Case Study Reporting on Cancer Survivors' and Program Staff's Experiences Within One Self-Management Support Intervention. (August 2020) - Brunet, Jennifer; Wurz, Amanda; Srivastava, Deeksha
Background. Cancer survivors must manage a range of adverse symptoms and side effects postdiagnosis. These effects often co-occur with preexisting comorbid conditions. Recognizing the complex chronicity of the disease, self-management support interventions have been developed to promote cancer survivors' knowledge, skills, and confidence to self-manage their health. Though shown to be beneficial, the processes underlying self-management have yet to be explicated. Aim. To explore how a community-based self-management support intervention fosters cancer survivors' knowledge, confidence, and skills to self-manage their health. Method. A qualitative case study adopting multiple viewpoints was utilized. Seventeen cancer survivors who participated in a self-management support intervention (referred to as a cancer coaching program) were interviewed and six program staff took part in a focus group. Transcripts from the interviews and focus group were analyzed using a hybrid inductive–deductive approach guided by principles of qualitative description. Results. Cancer survivors and program staff offered complementary perspectives that enhanced our understanding of how the self-management support intervention fosters cancer survivors' knowledge, confidence, and skills to self-manage their health. Four themes captured strategies necessary to promote self-management: (1) looking beyond the disease: the importance of holistic person-centered care, (2) cocreating plans: the key to effective and meaningful self-management support, (3) fostering activation via tailored, targeted, and expert-sourced information and resources, and (4) having dependable and impartial emotional support. Within each theme, pertinent self-management support strategies were described by cancer survivors and program staff. Discussion and Conclusion. Findings offer an understanding of how one community-based self-management support intervention promotes self-management and highlight valuable self-management support strategies that could be incorporated into existing and future interventions.